Istinbath Method of Tablighi Students In Pesantren Temboro: Textual and Contextual Matter - Sukron Mamun; Ilyya Muhsin (Justicia Islamica, 2020)
This article discusses istinbath (the way to absorb law from the primary sources) of fiqh (Islamic law) by Tablighi students (santri) at Pesantren Temboro, Magetan, East Java in bahsul al-masa’il forum that is a forum for discussing Islamic law problems. The exciting thing about this study is Temboro Tablighi students as a traditionalist group known as the traditional Islamic community and the followers of Jamaah Tabligh. The questions are: What are the types of Islamic thought and the kinds of istinbath used by Tablighi students? Is the istinbath in the bahsul al-masa’il forum the same as that of other students of traditional Pesantrens in Indonesia or not? This article answers those research questions not only to analyze how Tablighi students apply the istinbath model in their forum but also to analyze the bahsul al-masa’il products. This study is based on scoped library research i.e. the results of bahsul al-masa’il published in Tablighi students’ magazines during 2018, such as Al-Madinah, Al-Maktabah, Humairo, and Tranqil. One of the teachers involved in the forum is interviewed to clarify and get more detailed information. The study results show that the istinbath method of Tablighi students, in general, is the same as other traditional students in other pesantrens that only apply the qauliyyah method (using ulemas’ arguments written in classical books called Kitab Kuning). This study contributes significantly to how Tablighi santri of the Pesantren Temboro remain conserving a traditional scholarship knowledge (turats) with contextualization limitedly on some cases.